2012
DOI: 10.1063/1.3695998
|View full text |Cite
|
Sign up to set email alerts
|

Strain relaxation in single crystal SrTiO3 grown on Si (001) by molecular beam epitaxy

Abstract: An epitaxial layer of SrTiO3 grown directly on Si may be used as a pseudo-substrate for the integration of perovskite oxides onto silicon. When SrTiO3 is initially grown on Si (001), it is nominally compressively strained. However, by subsequent annealing in oxygen at elevated temperature, an SiOx interlayer can be formed which alters the strain state of SrTiO3. We report a study of strain relaxation in SrTiO3 films grown on Si by molecular beam epitaxy as a function of annealing time and oxygen partial pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 35 publications
1
46
0
Order By: Relevance
“…Choi et al showed that the SiO 2 interfacial layer thickness increased during post-deposition annealing as P(O 2 ) and/or annealing time were increased (annealing at 650 °C under P(O 2 ) from 2 × 10 −7 to 1 × 10 −5 Torr) [96] and that it can be used to tune the strain relaxation of the SrTiO 3 layer. Before annealing, the SrTiO 3 layers are expanded in-plane due to the bi-axial tensile strain exerted by Si during cooling down.…”
Section: Mbe Of Batio3 On Semiconductors: Growth and Crystalline Strumentioning
confidence: 99%
“…Choi et al showed that the SiO 2 interfacial layer thickness increased during post-deposition annealing as P(O 2 ) and/or annealing time were increased (annealing at 650 °C under P(O 2 ) from 2 × 10 −7 to 1 × 10 −5 Torr) [96] and that it can be used to tune the strain relaxation of the SrTiO 3 layer. Before annealing, the SrTiO 3 layers are expanded in-plane due to the bi-axial tensile strain exerted by Si during cooling down.…”
Section: Mbe Of Batio3 On Semiconductors: Growth and Crystalline Strumentioning
confidence: 99%
“…The Si wafer is first degreased and exposed to ultraviolet/ozone prior to loading into the growth chamber. After desorption of the native SiO 2 using a Sr-assisted deoxidation process [41], 50 Å of crystalline SrTiO 3 with TiO 2 termination is deposited on Si with the aid of a ½ monolayer Sr template [32,42] at a substrate temperature of 550°C and a background oxygen pressure of 4×10 -7 torr. The substrate temperature is then quickly increased to 650°C, while oxygen pressure is slowly ramped to 1×10 -6 torr for the anatase TiO 2 deposition.…”
Section: Methodsmentioning
confidence: 99%
“…Using MBE, we grow epitaxial c-axis oriented anatase on an STO/Si (001) pseudo-substrate [32], and use Z-contrast STEM to elucidate the real physical structure of the interface. EELS is used to probe the electronic structure across the interface.…”
Section: Introductionmentioning
confidence: 99%
“…The wafers were loaded into the MBE chamber where four unit cells of STO were deposited on Si(001) as described in more detail elsewhere. 22,23 . The LAO growth was also examined on 10 × 10 × 0.5 mm 3 STO(001) single crystal substrates from MTI.…”
Section: Methodsmentioning
confidence: 97%
“…The degree of compressive strain is a function of the annealing temperature and the thickness of the SiO 2 layer that can form at the interface between Si(001) and STO. 22 In the case of four unit cells annealed at less than 650 °C, the in-plane lattice constant of the STO film is the same as Si(001) spacing along the [110] direction. Films grown on the STO-buffered Si(001) substrate are strained to the Si(001) lattice spacing (3.84 Å).…”
Section: Introductionmentioning
confidence: 98%